Respons Fungsional Burung Pentet (Lanius sp.) terhadap Belalang Kembara (Locusta migratoria manilensis) - Siti Astuti; Kasumbogo Untung; F. X. Wagiman (Jurnal Perlindungan Tanaman Indonesia, 2009)
The functional response of predatory bird, Lanius sp. (Passeriformes: Laniidae) on migratory locust [Locusta migratoria manilensis (Orthoptera: Acrididae)] had been studied under restricted condition. The migratory locusts were reared in the green house. Second and fourth nymph instars along with adult stages of the migratory locust were used in this trial. Maximum feeding and functional response of the predatory bird against the migratory locust were determined. Research protocol used follows Holling’s model. Results showed that the maximum feeding of the predatory bird was very high i.e. against 2nd and 4th instars and adult of the locust were 2.75 preys/minute, 0.13 preys/minute, and 0.09 preys/minute; respectively. The relationship between predatory bird and migratory locust fitted with the Holling’ s type 2 functional response. The high feeding rate of the predatory bird revealed that the bird is a promising candidate of biological control agent on migratory locust.